Dipo Alam: Cermin Kepemimpinan dan Pencitraan SBY - Muslikhin (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2017)
Dipo Alam has so many times politicized the corruption cases for Susilo Bambang Yudhoyono (SBY ) interest, both as his capacity as president and the leader of Partai Demokrat (Democratic Party). The aim is clear, to up grade the image of SBY as an anti-corroption figure and to strengthen his position as the number one figure in Indonesia. Moreover, it also helps to picture that not only the members of Democratic Party who corrupt but also the members of other political parties. In fact, the leadership of SBY can be categorized as what so-called leisure leadership, for he often avoids substancial issues and it is common for him to care at lipstical matters.